THE REGIONAL HEAD ELECTION MODEL BASED ON THE 1945 CONSTITUTION IN THE CONTEXT OF REGIONAL AUTONOMY - Amancik Amancik (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTArticle 18 of the Constitution of 1945, is not set explicitly on the model either local elections before the change and after the change, giving rise to multiple interpretations. Legislature to interpret the model in accordance with the local elections of political will at the time. Prior to the 1945 changes in the regulation of local government such as the Act No. 5 of 1974, No. 22 of 1999, and after the 1945 changes governed by Act No. 32 of 2004 on regional governance. Setting the local elections in the legislation are inconsistencies between laws that regulate each other electoral models vary. The inconsistency of these legal norms have implications for the implementation of regional autonomy within the system of the Republic of Indonesia. Under the decentralized form an autonomous region, the system is essentially delegated to the local government administration (the law) is given the right to administer their own affairs of the household. The goal is for people to participate in democratic governance, inorder to realize social justice welfare in the area.Key words : Implications, Local Elections, Autonomy